Art of Our Century : The Chronicle of Western Art - 1900 to the Present. - Ferrier, Jean-Louis; Hulten, Pontus (New York - London - Toronto - Sydney - Tokyo : Prentice Hall Editions, 1989)
Aalto, Alvar ; Albers, Josef ; Appel, Karel ; Archipenko, Alexander ; Arman ; Arp, Hans (Jean) ; Bacon, Francis ; Balla, Giacomo ; Balthus ; Bazaine, Jean ; Beckmann, Max ; Beuys, Joseph ; Bissière, Roger ; Boccioni, Umberto ; Bonnard, Pierre ; Brancusi, Constantin ; Braque, Georges ; Buffet, Bernard ; Calder, Alexander ; César ; Chagall, Marc ; De Chirico, Giorgio ; Dali, Salvador ; Delaunay, Robert & Sonia ; Derain, André ; Dix, Otto ; van Dongen, Kees ; Dubuffet, Jean ; Duchamp, Marcel ; Dufy, Raoul ; Ernst, Max ; Fautrier, Jean ; Fontana, Lucio ; Francis, Sam ; Buckminster Fuller, Richard ; Giacometti, Alberto ; Gris, Juan ; Gropius, Walter ; Grosz, George ; Hartung, Hans ; Hélion, Jean ; Herbin, Auguste ; Hopper, Edward ; Hundertwasser ; Jawlensky, Alexej von ; Johns, Jasper ; Jorn, Asger ; Kandinsky, Wassily ; Kirchner, Ernst Ludwig ; Klee, Paul ; Klein, Yves ; Klimt, Gustav ; Kokoschka, Oskar ; de Kooning, Willem ; Kupka, Frantisek ; Lapicque, Charles ; Larionov, Mikhail ; Laurens, Henri ; Le Corbusier ; Leger, Fernand ; Lichtenstein, Roy ; Lipchitz, Jacques ; Lurçat, Jean ; Magritte, René ; Malevich, Kasimir ; Marquet, Albert ; Masson, Andre ; Mathieu, Georges ; Matisse, Henri ; Mies van der Rohe, Ludwig ; Miro, Joan ; Modigliani, Amedeo ; Moholy-Nagy, Laszlo ; Mondriaan, Piet ; Moore, Henry ; Morandi, Giorgio ; Motherwell, Robert ; Newman, Barnett ; Oldenburg, Claes ; Pevsner, Antoine ; Picabia, Francis ; Picasso, Pablo ; Pignon, Edouard ; Pollock, Jackson ; Rauschenberg, Robert ; Reinhardt, Ad ; Richier, Germaine ; Riivera, Diego ; Rothko, Mark ; Rouault, Georges ; Russolo, Luigi ; Schiele, Egon ; Schoffer, Nicolas ; Schwitters, Kurt ; Severini, Gino ; Soulages, Pierre ; Soutine, Chaim ; de Staël, Nicolas ; Tanguy, Yves ; Tàpies, Antoni ; etc.
Geselect. biog. p. 848-866
Overzicht stromingen p. 838-847
Engels
boek